Towards the Collaborative Governance in Maintaining Indigenous History of Pejangki Village in Indragiri Hulu, Indonesia - Raja Muhammad Amin; Auradian Marta (Department of Government Studies Universitas Muhammadiyah Makassar, 2021)
Pejangki Village is one of the villages that has managed to maintain its long-standing indigenous history. The argument from this study is that success in preserving indigenous history is the result of a multi-actor collaboration process within it. Therefore, this study seeks to explore collaboration among actors in maintaining indigenous history in Pejangki Village, Batang Cenaku District, Indragiri Hulu Regency, Riau Province. This study uses a qualitative approach with a focus on analyzing collaboration between state and non-state actors in the context of maintaining indigenous history in Pejangki Village. The data obtained were sourced from interviews and secondary data which included report results, journals, documents, and minutes of meetings. The results of this study indicate that collaboration among these actors can be successful because of the initial conditions that support collaboration, institutional design, multi-stakeholder participation and engagement, and facilitative leadership. The conclusion is that the policy of maintaining indigenous history in Pejangki Village is the result of the practice of collaborative governance carried out by state and non-state actors.